ANALISIS PERTUMBUHAN EKONOMI D.I. YOGYAKARTA TAHUN 2008-2016 - Hapsa, Sitti; Khoirudin, Rifki (EP FEB UNS, 2018)
One of the goals of regional development is to increase economic growth. The increasing economic growth of a region, will realize the level of welfare of its people. This study aims to determine the effect of local revenue, capital expenditure and labor on economic growth in the Province of DIY in 2008-2016. This research is an empirical research with panel data analysis tools. The data used in this study are secondary data from 5 regencies / cities in DIY Province in 2008-2016. The analysis model used in this study to estimate the regression model is to use the Random Effect model. The results in the study at the 5% significance level showed that: (1) the variables of regional income have a positive and significant effect on economic growth; (2) capital expenditure variables have a negative and insignificant effect on economic growth; (3) labor variables have a positive and significant effect on economic growth.Keywords: economic growth, regional income, capital expenditure and labor.JEL Classification : E01, H13